Biosorption of Cr(VI) by three different bacterial species supported on granular activated carbon: a comparative study - Quintelas, C. (2008)
The ability of three different bacterial species supported on granular activated carbon (GAC) to remove hexavalent chromium from low concentration liquid solutions was investigated, in batch and column studies. The microorganisms tested were Cr(VI) reducing types: Streptococcus equisimilis (CECT 926), Bacillus coagulans (CECT 12) and Escherichia coli (CECT 515). The results showed metal uptake values of 5.82, 5.35 and 4.12 mg/gbios., respectively, for S. equisimilis, B. coagulans and E. coli, for an initial metal concentration of 100 mg/l. In the same order and for the initial concentration of 50 mg/l, metal uptake values were 2.33, 1.98 and 3.60 mg/gbios.. Finally, for the initial metal concentration of 10 mg/l, those values were, respectively, 0.66, 1.51 and 1.12 mg/gbios.. Studies made with an industrial effluent, with the aim of testing these biofilms in a real situation, showed values of Cr uptake of 0.083, 0.090 and 0.110 mg/gbios., respectively, for S. equisimilis, B. coagulans and E. coli, for an initial concentration of 4.2 mg/l of total Cr. The quantification of polysaccharides, playing a key role in the whole process, was made and it was concluded that the production of polysaccharides is higher for B. coagulans followed by S. equisimilis and E. coli (9.19, 7.24 and 4.77 mg/gbios.). The batch studies data were described using the Freundlich, Langmuir, Redlich–Peterson, Dubinin–Radushkevich, Sips andToth model isotherms. The best fit was obtained with Sips and Toth model isotherms, respectively, for the S. equisimilis and for the B. coagulans biofilms. For the E. coli biofilm the Freundlich, Redlich–Peterson, Sips and Toth models fitted very well to the experimental data. The Adams–Bohart,Wolborska and Yoon and Nelson models were applied to column studies data. Those models were found suitable for describing the dynamic behaviour of the columns with respect to the inlet chromium concentration. Obtained results showed that the biofilms tested are very promising for the removal of Cr(VI) in diluted industrial wastewater. Despite differences in the cell wall structure and composition, the three bacteria exhibit comparable sorption affinities towards chromium, in the open systems studies. The Gram-positive bacteria tested (B. coagulans and S. equisimilis) presented best metal removal percentages in batch studies.